Unity and diversity in Christ : interpreting Paul in context : collected essays - Campbell, William S. (James Clarke & Co, 2017)
A collection of essays re-examining the writings and legacy of St Paul, emphasising the continuity between his epistles and his Jewish roots.
Keywords: Paul, -- the Apostle, Saint.; Bible. -- Epistles of Paul -- Criticism, interpretation, etc.; Paul, -- the Apostle, Saint; Bible. -- Epistles of Paul; Jews in the New Testament.; Judaism -- Relations -- Christianity.; Juifs dans le Nouveau Testament.; Judaïsme -- Relations -- Christianisme.; RELIGION -- Biblical Studies -- New Testament.; RELIGION -- Biblical Criticism & Interpretation -- New Testament.; Christianity; Interfaith relations; Jews in the New Testament; Judaism; Criticism, interpretation, etc.